Deterministic Kalman filtering on semi-infinite interval - L. Faybusovich (2018)
We relate a deterministic Kalman filter on semi-infinite interval to linear-quadratic tracking control model with unfixed initial condition. Copyright © 2012 L. Faybusovich and T. Mouktonglang.